2018
DOI: 10.1111/jocs.13767
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter mitral valve implantation for degenerated mitral bioprostheses or failed surgical annuloplasty rings: A systematic review and meta-analysis

Abstract: BackgroundTranscatheter mitral valve‐in‐valve (TMVIV) and valve‐in‐ring (TMVIR) implantation for degenerated mitral bioprostheses and failed annuloplasty rings have recently emerged as treatment options for patients deemed unsuitable for repeat surgery.MethodsA systematic literature review was conducted to summarize the data regarding the baseline characteristics and clinical outcomes of patients undergoing TMVIV and TMVIR procedures.ResultsA total of 245 patients (172 patients who underwent TMVIV surgery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 106 publications
3
41
0
3
Order By: Relevance
“…The introduction of transcatheter approaches to mitral valve disease will likely increase in higher risk patients undergoing reoperative surgery. These include valve‐in‐valve and valve‐in‐ring replacement via peripheral and transapical approaches . These techniques have been safe and effective short‐term, but long‐term data are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of transcatheter approaches to mitral valve disease will likely increase in higher risk patients undergoing reoperative surgery. These include valve‐in‐valve and valve‐in‐ring replacement via peripheral and transapical approaches . These techniques have been safe and effective short‐term, but long‐term data are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In certain patients with significant comorbidities, redo surgery may be associated with an early mortality as high as 5%–12% . In recent years, transcatheter valve‐in‐valve options have become available for such high‐risk individuals . These transcatheter valves are most often implanted through a transseptal approach which is less invasive than the transapical route as demonstrated in our patient .…”
Section: Discussionmentioning
confidence: 84%
“…The pathogenesis of bioprosthetic valve commissural fusion is uncertain. Vainrib et al have reported a 77‐year‐old woman who developed bioprosthetic mitral stenosis due to commissural fusion 6 months after implantation of a bovine bioprosthesis. She underwent percutaneous balloon valvuloplasty with redevelopment of stenosis 2 years after requiring transapical valve‐in‐valve prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality at 30 days was 6.5%, which was lower than the predicted operative mortality (STS‐PROM) of 8.9 ± 6.8%. In a meta‐analysis including a total of 245 patients undergoing VIV‐TMVR (70.2%) and VIR‐TMVR (29.8%), 30‐day mortality was 8.1%. In our meta‐analysis, observed 30‐day mortality was approximately two to threefold higher (20.4% versus 6.5% and 8.1%) compared with patients undergoing VIV‐TMVR and VIR‐TMVR.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis including a total of 245 patients undergoing VIV‐TMVR (70.2%) and VIR‐TMVR (29.8%), 30‐day mortality was 8.1%. In our meta‐analysis, observed 30‐day mortality was approximately two to threefold higher (20.4% versus 6.5% and 8.1%) compared with patients undergoing VIV‐TMVR and VIR‐TMVR. The reason for the higher 30‐day mortality in MR patients undergoing TMVR than patients undergoing VIV‐TMVR and VIR‐TMVR is unclear but may be related to a higher incidence of co‐morbidities in the native MR patients.…”
Section: Discussionmentioning
confidence: 99%